Investigation of Nonmotor Symptoms in First-Degree Relatives of Patients with Different Clinical Types of Parkinson’s Disease - Jiang-bing Liu; Jun-ling Leng; Ying-ge Wang; Yu Zhang; Tie-yu Tang; Li-hong Tao; Xin-jiang Zhang; Chun-feng Liu (Parkinson's Disease)
Background. Nonmotor symptoms (NMS) are prodromal characteristics of Parkinson’s disease (PD). The first-degree relatives (FDR) of PD patients had a higher risk of PD and also had more NMS. Objective. To delineate NMS in FDR of patients with different clinical types of PD. Methods. A total of 98 PD probands were recruited; 256 siblings of them were enrolled in the FDR group. Various scales were used to assess NMS, including depression, anxiety, cognitive impairment, insomnia, constipation, excessive daytime sleepiness, rapid eye movement sleep behavior disorder (RBD), and restless legs syndrome (RLS). The incidences of NMS were further compared between the FDR groups of PD with different types. Results. The FDR of early-onset PD (EOP) showed a higher incidence of moderate to severe depression (OR = 4.08; 95% CI: 1.12–14.92; P=0.033), anxiety (OR = 4.22; 95% CI: 1.87–9.52; P=0.001), and excessive daytime sleepiness (OR = 3.40; 95% CI: 1.00–11.48; P=0.049) than the FDR of late-onset PD (LOP). It was also found that RBD (OR = 11.65; 95% CI: 3.82–35.54; P<0.001), constipation (OR = 4.94; 95% CI: 1.85–13.21; P=0.001), sleep disorders (OR = 4.51; 95% CI: 1.73–11.78; P=0.002), cognitive impairment (OR = 3.55; 95% CI: 1.62–7.77; P=0.002), and anxiety (OR = 2.49; 95% CI: 1.32–4.71; P=0.005) were more frequent in FDR of tremor-dominant PD (TDP) than in FDR of non-tremor-dominant PD (NTDP). Conclusions. The siblings of patients with EOP and TDP have more NMS, presuming that they have a higher risk in the PD prodromal stage. Whether they have a greater possibility to progress into PD requires further investigation.